Analysis of factors affecting fraudulent financial reporting in fraud pentagon perspective (Lighthouse Publishing, 2023)
The data from ACFE show that Indonesia, in the 2014-2020 period, had 126 cases of fraud, ranking the country as the second-highest country with the most fraud cases in the Asia Pacific. This phenomenon attracts the author to investigate factors that encourage the emergence of fraudulent financial reporting from the perspective of the Fraud Pentagon theory. Although many studies have been done on this topic, the results of the previous studies have not shown any uniformity or, even, consistency between theory and empirical reality. This study focus on a similar topic, but with a different object and approach. The objects studied in this study are utility, transportation, and infrastructure companies listed on the Indonesia Stock Exchange in the 2015-2019 period; Meanwhile, for the testing technique, this research applies several computational techniques, ranging from the Classical Assumption Test to the hypothesis test using the IBM SPSS 25 analysis tool Data were obtained from 185 samples selected using the purposive judgment sampling method. The data, then, were analyzed using multiple linear regression analysis. The results of this study indicate that not all of the factors studied influence fraudulent financial reporting. Of the seven hypotheses proposed, only the financial target variable has a positive effect on fraudulent reporting. Similarly, the nature of the industry variable also influences fraud, but in the opposite direction (negative). Meanwhile, the other five variables, namely: external pressure, monitoring effectiveness, change in auditors, change in directors, and dual CEO positions do not indicate having significant influences. This study has several limitations, dealing with measurement techniques and the reliance on information attached to the company's financial statements, which might have been manipulated before. These limitations indicate that further research on this topic is needed to obtain better results.